Literary Networks and Digital Media in Contemporary African Literatures - Aurélie JOURNO (E-REA)
Building on recent research around digital cultural production in Africa (Ligaga, Adenekan, Nyabola), my paper seeks to engage with digital media and online spaces — blogs, social media — in relation to contemporary literary practices in Africa. Its aim is to examine issues surrounding the production and circulation of contemporary “digital-native” texts, as well as the networks, both virtual and material, that underlie them. It draws on a range of examples from contemporary anglophone Africa, from online magazines (Bakwa, Saraba, Jalada, Hekaya) and Facebook fiction to self-published popular novels by writers who use social networks and blogs to produce, advertise and circulate their work (like Nigerian writer Myne Whitman and South African novelist Dudu Busani-Dube).First, the paper examines the complex relationship contemporary digital productions bear to the materiality and literary value usually associated with print. It then seeks to question the widespread notion that digital spaces are unmoored to geography and unbound by the power structures of the print publishing sector. Lastly, by analyzing two recent initiatives from Kenya (Jalada and Hekaya), it focuses on the various scopes and geographies of these virtual literary networks and the ways in which they intersect with material and social networks, through events like festivals or writers’ workshops.